Pengaruh Variabel Makroekonomi terhadap Tabungan Masyarakat: Studi Kasus Provinsi Sumatera Utara - Ulhaq Hasbi, Zia; Febriaty, Hastina; Rahayu, Sri Endang; Safina Hasibuan, Lailan (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2025)
The purpose of this study is to evaluate and analyze the effect of inflation, consumption, and per capita income on savings in North Sumatra Province. The method in this study uses an associative approach, which involves the explanation of variables. Time series data used from 2019 to 2023. The independent variables in this study are per capita income, inflation, and consumption while the dependent variable is the savings variable. In this study, the data analysis technique uses the Common Effect Model or Pool Least Square (CEM) method using multiple regression with the Pool Least Squares method. The results show that per capita income has a positive and significant effect on savings in North Sumatra Province. Inflation has a positive but insignificant effect on savings in North Sumatra Province. Consumption has a positive but insignificant effect on savings. And simultaneously per capita income, inflation and the economy together have a significant effect on savings in North Sumatra.